EFFECT OF CONSOLIDATION POLICY IN NIGERIAN BANKING INSTITUTIONS ON AGRIBUSINESS SECTOR PERFORMANCE (1995-2014) - Chinonso Henry ENE; Joseph ONWUMERE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The broad objective of this study was to analyze the effects of consolidation policy in Nigerian banking institutions on agribusiness sector performance. The specific policies of interest were merger and acquisition policy. The study covered 1995-2014 periods. Secondary data from CBN annual reports and statement of accounts, CBN bulletin and National Bureau of Statistics were used for the study. The data were analyzed by the use of regression models. Findings revealed that merger and acquisition consolidation policy in the Nigerian banking institutions, value of banks loan to agribusinesses, lagged value of national savings, population, rainfall and government capital investment to agribusiness sector significantly influenced agribusiness output in Nigeria within the study period. Merger and acquisition consolidation policy in the Nigerian banking institutions, external reserve, capital formation and agricultural export significantly influenced government credit allocation to agribusinesses in Nigeria within the study period. Merger and acquisition consolidation policy in the Nigerian banking institutions, exchange rate, rate of domestic utilization capacity for agribusiness commodities and population significantly influenced agribusiness export growth in Nigeria within the study period. The study concluded that merger and acquisition consolidation policy in the Nigerian banking institutions influenced the agribusiness sector performance as it leads to increase in both agribusiness output and government credit allocation to agribusinesses in Nigeria but did not lead to increase in agribusiness export growth. The study recommended that consolidation policy of the Nigerian banking institutions which led to increase in credit allocation to agribusinesses in Nigeria as well as improved agribusiness output must be sustained by the Central Bank of Nigeria and even made better in such manners that agribusiness output will grow and allow the country to make huge foreign income from agribusiness export especially now that the revenue from oil is on the decrease in the country.